Professor training in health postgraduate studies: analysis of an experience - Wanderlei Abadio de Oliveira; Jorge Luiz da Silva; Neire Aparecida Machado Scarpini; Susana Segura Munõz; Marta Angélica Iossi Silva; Marlene Fagundes Carvalho Gonçalves (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To analyze a professor training experience for higher education. Method: This is a descriptive case report on the professor training process in the postgraduate course of the College of Nursing of Ribeirão Preto, University of São Paulo. An evaluative activity was performed to capture the perceptions and experiences of 21 graduate students who were interns of an educational improvement program. The data were analyzed following the thematic content analysis guidelines. Results: Three thematic categories were identified: 1) knowledge necessary for teaching practice; 2) teaching routines and practices; 3) the essentiality of mentoring. Final considerations: This article provides a critical approach on the formative process of human resources for higher education in health, identifying potentials and challenges. Its innovative character resides in understanding pedagogical work articulated with graduate research training.